A conceptual design of novel modern random key-stream generator for high immunity correlation attack - Al-Abiachi, Ashwak M.; Ahmad, Faudziah; Ku-Mahamud, Ku Ruhana (2011)
Recently, the rapid development and the common use of electronic data processing administered through the Cyberspace, cooperatively with many incidents of attacks and breaches, fuelled the need for better methods of defending the computers and the information they store, process, and transmit. According to these difficulties, this research seeks to design a novel modern key-stream generator for high immunity correlation attacks. The research stated the main components of the proposed method, which divided into three diminutions RMA, MFSR & VLFCSR, and PER with 32 number to diffuse the output.